PEMBERDAYAAN DAN INOVASI UNTUK KEMANDIRIAN DESA - Jepinus; Fitrian, Yuko (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2024)
This empowerment program titled "Empowerment and Innovation for Village Self-Reliance" aims to enhance the capabilities of rural communities by fostering local innovation and sustainable economic practices. Through a series of training sessions, technical skills development, and entrepreneurial mentoring, the program enables village communities to utilize their local resources effectively and create economic opportunities within the village. This approach not only promotes self-reliance but also reduces dependence on external resources, creating a resilient local economy. The results of the program demonstrate improved knowledge, skills, and confidence among participants in developing market-relevant products and services. The community’s active involvement in managing village resources and implementing innovative solutions significantly contributes to sustainable development. To ensure long-term impact, recommendations include continuous training aligned with market trends, improved access to funding and marketing channels, and the establishment of partnerships with private and public sectors to support distribution and market expansion. Overall, the program serves as a strategic initiative to foster village independence and economic growth.